Growth in captivity of Crocodylus acutus (Cuvier, 1807) in Tumbes, Peru - Pérez, Oswaldo (2007)
A group of 40 individuals of C. acutus by captive reproduction maintained in the Centro de Acuicultura La Tuna Carranza, localed en Puerto Pizarro, Departamento de Tumbes was used to evaluate the growth. Comparations between size class of crocodiles showed that growth in length are not different, but growth in weight are different. The mean growth in length and weight was 1,44% and 0,18% in hatchling, 1,30 and 0,10% in yearlings, 1,24 and 0,22% in juveniles, 1,24 and 0,48% in subadults, and 1,01 and 0,75% in adults. The growth rate of females was highest that males.